Improving Learning Outcomes of Side Kick in Pencak Silat through Command Teaching Style and Learning Variations - Ayu Mutiara Sari; Afri Tantri; Ramadan Ramadan; Alan Alfiansyah Putra Karo Karo (Journal Of Sport Education (JOPE), 2025)
This study aimed to improve students’ learning outcomes of the side kick technique in pencak silat through the application of the command teaching style and learning variations among Grade XI MIA 3 students of SMA Negeri 3 Medan in the 2019/2020 academic year. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research instruments included a portfolio-based assessment covering the initial stance, execution, and final stance of the side kick technique, as well as a learning outcomes test at the end of each cycle. The findings indicated an improvement in students’ mastery learning, from the initial data of 38.89% (14 students) to 52.78% (19 students) in Cycle I with an average score of 84.7 and further increased in Cycle II to 88.89% (32 students) with an average score of 91.9. Therefore, the implementation of the command teaching style and learning variations can improve learning outcomes of the pencak silat side kick technique among Grade XI MIA 3 students of SMA Negeri 3 Medan.